2004
DOI: 10.1002/polb.20163
|View full text |Cite
|
Sign up to set email alerts
|

Statistical thermodynamics evaluation of polymer–polymer miscibility

Abstract: The Simha and Somcynsky (S–S) statistical thermodynamics theory was used to compute the solubility parameters as a function of temperature and pressure [δ = δ(T, P)], for a series of polymer melts. The characteristic scaling parameters required for this task, P*, T*, and V*, were extracted from the pressure–temperature–volume (PVT) data. To determine the potential polymer–polymer miscibility, the dependence of δ versus T (at ambient pressure) was computed for 17 polymers. Close proximity of the δ versus T curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…During the last two decades the simultaneous least-squares (lsq) fit of all data to S-S eos has been employed, Thus for example, Scientiste from MicroMath has been used [14][15][16][17][18][19][20]. Rapid convergence is obtained in two-steps: (1) fitting data to the polynomial expression [16],Ṽ ZṼðP;TÞ, provides the initial values of P*, T*, and V*, and then (2) fitting the data to the coupled Eqs.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…During the last two decades the simultaneous least-squares (lsq) fit of all data to S-S eos has been employed, Thus for example, Scientiste from MicroMath has been used [14][15][16][17][18][19][20]. Rapid convergence is obtained in two-steps: (1) fitting data to the polynomial expression [16],Ṽ ZṼðP;TÞ, provides the initial values of P*, T*, and V*, and then (2) fitting the data to the coupled Eqs.…”
Section: Theorymentioning
confidence: 99%
“…The S-S theory has been used to provide description of the cohesive energy density [14,15], internal pressure, PVT behavior [16][17][18][19][20], etc. The great advantage of the S-S derivation is direct incorporation of the free volume parameter, h, which in turn may be used to interpret variety of dynamic properties, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…(2.30) suggests that minimization of the enthalpic term might provide the necessary condition for miscibility [190]. The required characteristic scaling parameters, , and , are readily extracted from the , data.…”
Section: Generalmentioning
confidence: 99%
“…A theoretical derivation based on Eq. (2.29) indicated that solvent may increase the macromolecular mobility equivalent to that found at a temperature about 300 C higher than the glass transition temperature, that is, at g 300 [190].…”
Section: Generalmentioning
confidence: 99%
“…The discrepancy originates in the solubility method used to determine the δ value of high polymers. The extra free volume introduced by solvents increases the polymer free volume, equivalent to heating it to T ≥ T g + 300 K [Utracki, 2004a;Utracki and Simha, 2004] FIGURE 6.2 Compressibility parameter for PS; monotonic increase of κ with T is observed only at T > 1.2T g,P=0 . The transitory behavior at T g ≤ T ≤ 1.2T g is invisible in Figure 6.1.…”
Section: Ced Of a Single Componentmentioning
confidence: 99%